Characterization of Nucleobases in Broadband Terahertz Spectra from 0.5 to 10 THz with the Air-Biased-Coherent-Detection Technique - Miao Yu (Sensors, 2019)
Terahertz time-domain spectroscopy (THz-TDS) is an effective coherent detection technique for deeply understanding the structures and functions of biomolecules. However, generally not full information in the whole THz range can be obtained due to the limited detection bandwidth (usually less than 5 THz) of the traditional THz-TDS systems. In this paper, effective THz absorption spectra in 0.5–10 THz range of five typical nucleobases of DNA/RNA are characterized with a super broadband THz detection technique, called the air-biased- coherent-detection (THz-ABCD) technique. Few unexpected characteristic absorption peaks appeared in the low-frequency region and meanwhile a series of anticipated characteristic absorption peaks are found in the high-frequency region. The fingerprint spectra of these nucleobases are helpful for further analysis on the vibration and twisting behavior of hydrogen bonds, van der Waals and electrostatic forces etc. between and within DNA/RNA biomolecules.